Perbandingan Efektivitas Salin Normal dengan Udara dalam Pengembangan Balon Pipa Endotracheal untuk Mengurangi Risiko Sakit Tenggorokan Pascaintubasi - Adhriyani, Dessy; Harimin, Kusuma; Saleh, Irsan (Majalah Anestesia dan Critical Care, 2014)
Membandingkan efektivitas penggunaan saline normal dan udara dalam pengembangan balon pipa endotrakeal untuk mengurangi risiko sakit tenggorokan pascaintubasi pada pasien yang mendapatkan anestesi umum inhalasi dan N2O. Penelitian ini merupakan uji klinik secara tersamar buta ganda terhadap 70 pasien dengan status fisik American society of anesthesiologist (ASA) I-II yang akan menjalani anestesi umum. Pasien dibagi dalam dua kelompok dengan jumlah masing-masing 35 pasien. Kelompok pertama menggunakan udara sebagai media pengembangan balon pipa endotrakeal, sedangkan kelompok kedua menggunakan saline normal. Rasa nyeri dinilai dengan mengunakan skala VAS. Hasil dari penelitian menunjukkan bahwa rata-rata tekanan balon pipa endotrakeal pada kelompok salin normal lebih rendah dibandingkan dengan kelompok media udara dimana rata-rata tekanan balon selama operasi pada kelompok salin normal 26,71±0,92 mmHg dengan rata-rata VAS adalah 0,91±1,29 cm sedangkan pada kelompok media udara 34,63±4,81 mmHg dengan rata-rata VAS adalah 2,37±1,190 cm (p<0,0001). Penggunaan salin normal lebih efektif dibandingkan dengan media udara dalam pengembangan cuff ETT untuk mengurangi risiko sakit tenggorokan pascaintubasi pada pasien yang mendapatkan anestesi umum inhalasi dan N2O. Kata kunci: Sakit Tenggorokan, salin normal, udara Comparison between The Effectiveness of Normal Saline and Air With The Expansion of Endotracheal Tube Cuff to Reduce The Risk of Sore Throat Postintubation To compare the effectiveness of using normal saline and air medium with the expansion of endotracheal tube cuff to reduce the risk of sore throat postintubation in patients under general anesthesia using N2O.Method. This study is a randomized controlled trial with double blind method. Total patients are 70, ASA I-II status with general anestesi. Patients divided into 2 groups, where each group composed of 35 patients. The first group will be using air as a media inflation of cuff ETT, and the second group uses normal saline. The pain is examined using VAS.The result shows that mean pressure of intracuff in normal saline group is lower than media air group where there is intracuff mean pressure undergoing surgery in normal saline group is 26,71±0,92 mmHg with VAS 0,91±1,29 cm but for media air group 34,63±4,81 mmHg with VAS 2,37±1,190 cm where p<0,0001.The using of normal saline is more effective compared to air medium in the expansion of ETT cuff to reduce the risk of sore throat postintubation in patients under general anesthesia using N2O. Key words: Air, normal saline, sore throat Dullenkopf A, Gerber AC, Weiss M. Nitrous oxide diffusion into tracheal tube cuffs: comparison of five different tracheal tube cuffs. Acta Anaesthesiol Scand. 2004;48:1180–40. Morgan GE, Mikhail MS, Murray MJ. Airway management. Dalam: Clinical Anesthesiology. Edisi Ke-4. McGraw-Hill Companie. 2006. Hlm. 91–116. Fine GF, Borland LM. The future of the cuffed endotracheal tube. Pediatric Anesthesia. 2004;14: 38–42. Prerana P, Shroff, Vijay P. Efficacy of cuff inflation media to prevent postintubation related emergence phenomenon: air, saline and alkalinized lignocaine. Eur J Anaesthesiol. 2008;18:458–60. Nguyen H, Saidi N, Lieutaud T, Duvaldestin P. Nitrous oxide increases endotracheal cuff pressure and the incidence of tracheal lesions in anesthetized patients. Anesth Analg. 1999;89:187–90. Cerqueiera JR, Camacho LH, Takata IH. Endotracheal tube cuff pressure: need for precise measurement. Sao Paulo Med J/Rev Paul Med. 1999;117(6):243–7. Felten ML, Schmautz E, Orliaguet GA, Carli PA. Endotracheal tube cuff pressure 2003;97:1612–16. Karasawa F, Ozhima T, Takamatsu I, Uchihashi Y dkk. The effect on intracuff pressure of various nitrous oxide concentration used for inflating an endotracheal tube cuff. Anesth Analg. 2000;91:708–13. Karasawa F, Takita A, Mori T, Takamatsu I at all. The brandtm tube system attenuates the cuff deflationary phenomenon after anesthesia with nitrous oxide. Anesth Analg. 2003;96:606–10. Fitriyadi D, King LS. A simple endotracheal tube cuff pressure measuring device: an inexpensive alternative [Thesis]. Manilla: Santo Tomas University Hospital; 2004. Devys JM, Schauvliege F, Taylor G, Plaud B. Cuff compliance of pediatric and adult cuited tracheal tubes: an experimental study. Pediatric Anesthesia. 2004;14:676–80. Karasawa S, Okuda T, Mori T, Oshima T. Maintenance of stable cuff pressure in the Brandttm tracheal tube during anaesthesia with nitrous oxide. Br J Anaesth. 2002; 89(2):271–6. Fagan C, Frizelle HP, Laffey J, dkk. The effects of intracuff lidocaine on endotracheal-tubeinduced emergence phenomena after generalanesthesia. Anesth Analg. 2001;92:1075. Bennett MH, Isert PR, Cumming RG. Postoperative sore throat and hoarseness following tracheal intubation using air or saline to inflate the cuff–a randomized controlled trial. Anaesth Intensive Care. 2000;28:408–13. Raeder JC, Borchgrevink PC, Sellevold OM. Tracheal tube cuff pressures. The effects of different gas mixtures. Anaesthesia. 1985;40:444–7. Karasawa F, Tokunaga M, Aramaki Y, saizukuisai M, Satoh T. An assassment of a method of inflating cuffs with nitrous oxide mixture to prevent on increase in intracuff pressure in five different tracheal tube designs. Anesthesia. 2001;56:155–9. Morgan GE, Mikhail MS, Murray MJ. The Practice of anesthesiology. Dalam: Clinical Anesthesiology.4th ed. McGraw-Hill Companies, Dalam;2006. Hlm. 1–9. Darsch JA, Darsch SE. Tracheal tubes. In: Understanding anesthesia equipment penyunting. edisi ke 4. Williams and Wilkins Pennsylvania; 1999. Hlm. 557–635. Combes X, Schauvliege F, Peyrouset O, etal. Intracuff pressure and tracheal morbidity: influence of filling with saline during nitrous oxide anesthesia. Anesthesiology. 2001;95:1120–4. Mitchell V, Adams T, Calder I. Choice of cuff inflation medium during nitrous oxide anaesthesia. Anaesthesia. 1999; 54: 32–6. Hata TM, Moyers JR. Preoperative evaluation and management. Dalam: Barash PG, Cullen BF, Stoelting RK, penyunting. Clinical Anesthesia. Edisi ke-5. Lippincott Williams and Wilkins; 2006. Hlm. 475–9.